2006
DOI: 10.1289/ehp.8464
|View full text |Cite
|
Sign up to set email alerts
|

Blood Mercury Reporting in NHANES: Identifying Asian, Pacific Islander, Native American, and Multiracial Groups

Abstract: IntroductionAsians, Pacific Islanders, and Native Americans are a potentially high-risk group for dietary exposure to methylmercury through fish consumption. However, blood mercury levels in this group have not been identified in recent reports of the National Health and Nutrition Examination Survey (NHANES) for the years 1999–2002.MethodsWe used NHANES data from 1999–2002 to obtain population estimates of blood mercury levels among women of childbearing age classified as belonging to the “other” racial/ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 37 publications
3
60
2
Order By: Relevance
“…Data from the National Health and Nutrition Examination Survey demonstrated that mercury concentrations are significantly higher in Asians and Native American/Pacific Islanders (28). These findings are consistent with data showing higher rates of fish consumption in these groups.…”
Section: Figuresupporting
confidence: 83%
“…Data from the National Health and Nutrition Examination Survey demonstrated that mercury concentrations are significantly higher in Asians and Native American/Pacific Islanders (28). These findings are consistent with data showing higher rates of fish consumption in these groups.…”
Section: Figuresupporting
confidence: 83%
“…12, 16 These results highlight the need for further studies focused on immigrants and underscore the importance for health care professionals to provide personalized clinical evaluations and advice in ethnically diverse Canada. 17 The findings of increasing blood THg levels with increasing income and education level are consistent with data from other studies.…”
mentioning
confidence: 97%
“…consumption rates than the general US population (Hightower et al 2006;Shilling et al 2010). The model assumes that 100% of fish consumption comes from the stream being modeled.…”
Section: Fish Intake and Consumption Advisoriesmentioning
confidence: 99%